Diagnostic Analysis of Newman’s Types of Students’ Error in Finishing Questions of Mathematical Problem Solving - Muttaqi, Uzlifa Khanifatul; Kartono, Kartono; Karomah Dwidayanti, Nur (Unnes Journal of Mathematics Education Research, 2021)
This study was aimed at understanding the diagnostic description of the students' errors types according to Newman in solving the questions of mathematical problem-solving. This study was qualitative. Purposive sampling was used in this study that based on Newman's theory of five errors' types, namely reading error, comprehension error, transformation error, process skill error, and encoding error. The instruments used in this study were the test of the ability to solve mathematical problem and interview. The subject of the study was grouped based on the errors conducted by the eighth-grade students of MTs Al Ma’arif Rakit in solving the question. The result showed that the students' error was varied. The diagnostic results showed that among the 26 students who did four exercises of mathematical problem solving, 3 students did the reading error, 6 students did the comprehension error, 7 students did the transformation error, 9 students did the process skill error, and 11 students did the encoding error.